Konsep dan Tantangan Zona Kuliner Halal Aman dan Sehat Perspektif Maqasid Al-Syariah - Sovi Santri Susanti; Nurjannah Septyanun; Yulias Erwin (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
The existence of a halal, safe and healthy culinary zone is one of the things that supports economic development. With the existence of a halal culinary area, we can provide services that can guarantee that the food and drinks consumed are halal, healthy and comfortable for visitors. Consuming halal, safe and healthy food is a consumer's right, regardless of ethnicity, race, religion or economy. The halal, safe and healthy culinary zone is not only a place to eat, but also a tourist destination. The aim of this research is to analyze the concept and challenges of the Safe and Healthy Halal Culinary Zone from the Maqashid Al-Syariah perspective. This research uses qualitative research methods, namely research that aims to gain understanding, develop theories, and describe complex related problems. The sources used in qualitative research are only secondary data consisting of written form (library), including primary legal materials, secondary legal materials and tertiary legal materials. This research also uses a conceptual approach and a statutory approach. The results of the research are that the challenges faced by Indonesia are the lack of halal awareness among Indonesian society, the existence of problems in implementing the Halal Product Guarantee Law and the low awareness of Indonesian society to compete. Through this research, it is hoped that many groups will become increasingly aware of the importance of the halal industry so that they can support efforts to advance the Indonesian halal industry. By looking at these potentials and challenges, the government is advised to further promote education for business actors about the importance of maintaining and guaranteeing the quality of goods and services offered to the public, especially regarding guarantees of halalness considering that the majority of Indonesia's population is Muslim. Apart from that, there needs to be assistance for Micro, Small and Medium Enterprises (MSMEs) in the halal certification process.conclusions. 250 words maximum. Abstract should only be typed in one paragraph and in one column format.